Exosomal miR‐3180‐3p inhibits proliferation and metastasis of non‐small cell lung cancer by downregulating FOXP4. Issue 3 (21st December 2020) - Chen, Tengfei; Liu, Yali; Chen, Jun; Zheng, Huifei; Chen, Qiuyun; Zhao, Jun
Abstract : Background: Non‐small cell lung cancer (NSCLC) is one of the most malignant cancers worldwide and its pathogenesis is not completely clear. In this study, we explored the functions and mechanisms of exosomes transferring miR‐3180‐3p in NSCLC progression. Methods: The expression levels of miR‐3180‐3p in NSCLC tissues and paracarcinoma tissues was obtained from the GEO database (GEO: GSE53882). Exosomes derived from A549 cells were identified. Proliferation, migration and invasion were measured after treatment with exosomal miR‐3180‐3p or transfection using miR‐3180‐3p mimics. The relationship between miR‐3180‐3p and forkhead box P4 (FOXP4) was predicted using a bioinformatic tool and measured using a dual‐luciferase reporter gene assay and western blotting. Finally, a mouse xenograft model of NSCLC cells was established to verify the function of exosomal miR‐3180‐3p in vivo. Results: We found that miR‐3180‐3p decreased in both NSCLC cell lines and patient tissues. Overexpression of miR‐3180‐3p or treatment with exosomal miR‐3180‐3p significantly suppressed cell proliferation and metastasis in NSCLC cell lines. Subsequently, we found miR‐3180‐3p downregulated FOXP4 protein expression levels. Furthermore, the volumes and weights of nude mouse tumors expressing exosomal miR‐3180‐3p were significantly reduced. Conclusions: Exosomal miR‐3180‐3p suppresses NSCLC progression by downregulating FOXP4 expression. Key points: Significant findings of the study: We found that exosomal miR‐3180‐3p suppressed NSCLC progression and also identified a miR‐3180‐3p target gene. These findings provide a foundation to determine innovative therapeutic strategies. What this study adds: This study contributes to research investigating exosomal containing miRNAs. Abstract : We found that exosomal miR‐3180‐3p suppressed NSCLC progression and also identified a miR‐3180‐3p target gene.